Chemotherapy induced right ventricular cardiomyopathy; a systematic review and meta-analysis - Theetha Kariyanna, Pramod; Kumar, Ashish; Jayarangaiah, Amog; Shetty, Mrinali; Chowdhury, Yuvraj; Das, Sushruth; Jayarangaiah, Apoorva (Frontiers in Cardiovascular Medicine, 2023)
Background Left ventricular dysfunction and cardiomyopathy are well documented adverse effects associated with chemotherapy agents. Limited information exists regarding the impact of chemotherapeutic agents on the integrity and function of the right ventricle (RV). Objectives The current metanalysis compared pre- chemotherapy versus post- chemotherapy RV parameters measured on 2D echocardiography in patients receiving anthracycline and/or trastuzumab across all breast cancer patients. Methods A systematic search across PubMed, EMBASE and Cochrane databases were performed from inception of the databases until November 2021 for relevant studies. We used the inverse variance method with a random effect model and DerSimonian and Laird method of Tau2 generation to calculate mean difference [MD] with 95% confidence interval [CI]. The analysis was carried out using RevMan Version 5.3 (Copenhagen: The Nordic Cochrane Centre, The Cochrane Collaboration, 2014). Results Fifteen studies, constituting total of 644 patients, met the inclusion criteria, with most studies having a follow up period of less than 12 months from initiation of chemotherapy. Anthracycline and/or Trastuzumab chemotherapy resulted in a statistically significant reduction in right ventricular ejection fraction (RVEF) at follow-up [MD: 2.70, 95% CI: 0.27 to 5.13, P-value- 0.03, I2- 71%, χ2P-value < 0.05]. Treatment with Anthracycline and/or Trastuzumab chemotherapy resulted in a significant reduction in RV fractional area change (RVFAC) at follow-up [MD: 3.74, 95% CI: 1.33 to 6.15, P-value < 0.01, I2- 68%, χ2P-value < 0.05]. RV free wall longitudinal strain (RVFWLS) was lower at baseline, while LVEF was significantly reduced at follow-up [MD: -1.00, 95% CI: -1.86 to -0.15, P-value < 0.05, I2- 0%, χ2P-value-0.40], [MD: 4.04, 95% CI: 2.08 to 6.01, P-value < 0.01, I2- 91%, χ2P-value < 0.05], respectively. However, treatment with Anthracycline and/or Trastuzumab chemotherapy had no statistically significant effect on Tricuspid annular plane systolic excursion (TAPSE) at follow-up [MD: 0.53, 95% CI: -0.11 to 1.17, P-value-0.11, I2- 98%, χ2P-value < 0.05]. Conclusions Chemotherapy with anthracyclines and trastuzumab negatively affects right ventricular function leading to decline in RVEF, RVFAC, RVFWLS and LVEF.